Takhallī sebagai Coping Stres Akademik: Studi terhadap Mahasiswa Tadris Biologi UIN Raden Mas Said Surakarta - Silva Amelia Darrohmah; Rahdatu Cahya Puranita; Arzaq Danda Ikhtibar Mahardika (ALSYS, 2026)
Academic stress is a problem frequently experienced by students due to the high demands of lectures, assignments, practicums, and academic achievement targets. Students of Tadris Biologi at UIN Raden Mas Said Surakarta are vulnerable to stress because they must engage in theoretical learning and practicum activities simultaneously. This study aims to identify the factors causing academic stress and analyze the relevance of the concept of takhallī in Sufism as a strategy for managing academic stress among Tadris Biologi students at UIN Raden Mas Said Surakarta. This study used a qualitative approach, with data collected through online semi-structured interviews using WhatsApp with eight students from the 2023, 2024, and 2025 cohorts. The data were analyzed through the stages of data reduction, triangulation, and conclusion drawing. The results showed that the main factors causing academic stress included numerous assignments, practicum reports, a dense lecture schedule, and psychological pressure. The effects of stress experienced by students included fatigue, anxiety, lack of sleep, burnout, and decreased learning motivation. To address these problems, students applied various coping strategies, with a tendency to view spiritual-based coping as the most effective in providing inner calm. These strategies included prayer, dhikr, and the application of takhallī values, such as patience, tawakkal, and muhasabah. The conclusion of this study affirms that the concept of takhallī is relevant as a psychospiritual approach to academic stress management because it helps students control emotions, reduce anxiety, and build mental resilience in facing academic pressure. These findings imply the importance of integrating Sufi values into strengthening students’ psychological well-being in Islamic higher education settings.